Effects of climate adaptation on technical efficiency of maize production in Northern Ghana - William Adzawla; Hamdiyah Alhassan (Agricultural and Food Economics, 2021)
Climate adaptation is an essential strategy for responding to climate change at local levels and required for sustainable food production to meet the growing food demand. In this light, this study analyzed the effects of climate adaptation strategies on technical efficiency of maize farmers in Northern Ghana. This involved a total of 619 maize farmers that were selected through a multistage sampling procedure. A Cobb-Douglas stochastic frontier was fitted to the data. From the result, the major climate adaptation strategies adopted by the farmers include row planting, changing planting date, mixed farming, refilling, and intercropping. The frontier result shows that while climate adaptation significantly leads to higher maize outputs, only crop rotation and row planting significantly improve technical efficiency of maize farmers. Other factors that significantly influence maize output are farm size, labor, seed, and chemicals. The study concludes that climate adaptation, particularly, crop rotation and row planting, remains essential adaptation strategies for sustainable food production in the region. However, further understanding of mechanisms through which majority of the climate adaptation strategies significantly reduce technical efficiency is required.
Keywords: 330; Climate adaptation; Climate change; Maize production frontier; Northern Ghana; Technical efficiency